Homology-Directed Repair in Zebrafish: Witchcraft and Wizardry? - Prill, Kendal; Dawson, John F. (Frontiers in Molecular Biosciences, 2020)
Introducing desired mutations into the genome of model organisms is a priority for all research focusing on protein function and disease modeling. The need to create stable mutant lines has resulted in the rapid advancement of genetic techniques over the last few decades from chemical mutagenesis and zinc finger nucleases to CRISPR and Homology Directed Repair. However, achieving consistently high success rates for direct mutagenesis in zebrafish remains one of the most sought-after techniques in the field. Several genes have been modified using HDR in zebrafish, but published success rates range widely suggesting that an optimal protocol is required. In this review, we compare target genes, techniques and protocols from 50 genes that were successfully modified in zebrafish using HDR to find the statistically best variables for efficient HDR rates.